PELATIHAN CABANG OLAHRAGA BULU TANGKIS PADA PB DAREK - Burhan, Zakir; Herlina, Herlina; Nulhadi, Agus (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
Badminton is one of the sports that are the pride of the Indonesian nation. Badminton players will be very influential if they improve their playing skills. No less important for society in general, physical education lecturers at the Nusantara Global Institute of Education conduct training for the community to broaden and add to the knowledge of sports practitioners. By doing this, it is hoped that they will provide coaches and badminton players with an understanding of the importance of long-term training programs in badminton.